A Patient and Public Engagement Project to Inform Dementia Care in a UK Hospital Trust - Rachel K. Marrow; Camille Cronin; Victor Ashby; Thomas Currid; Marie Alexander (Wiley, 2024)
ABSTRACT Introduction The increasing prevalence of dementia in the United Kingdom presents significant challenges for healthcare, with projections estimating over a million affected individuals by 2025, costing the NHS £6.3 billion annually. Hospital admissions among dementia patients are common, occupying about 25% of UK hospital beds and leading to prolonged stays and diminished health outcomes. Method This paper presents the opening stages, part of a larger project where Patient and Public Involvement and Engagement (PPIE) was employed to understand and navigate what it means for hospital care for a person living with dementia. To understand hospital care for dementia patients, focus groups were conducted through dementia cafés in Essex and Suffolk from February to July 2023 engaging patients, carers and family members. Results Recognised processes for reporting PPIE and thematic analysis were used and identified six themes and 21 subthemes regarding hospital care: individualised care, role of carers, basic care, interpersonal communication, information sharing and staffing. Discussion The results from the PPIE will be used to inform and work with stakeholders through the next phases of the project, which involves examining care processes in the hospital, identifying touchpoints and evaluating these areas. The project continues to be informed by stakeholders including people living with dementia, carers and staff. Additionally, the results may inform other service providers for care enhancements, processes and delivery. Conclusion Moving forward, the study emphasises the importance of building collaborative relationships with stakeholders involved in dementia care. Additionally, it provides insights to focus areas that are fundamental for acute care organisations when delivering care to people living with dementia. By incorporating insights from PPIE, this project seeks to identify inequalities in dementia care services, improve hospital care for people living with dementia, fostering a more inclusive and supportive healthcare environment. Patient or Public Contribution The purpose of the study was to explore the most important issues around hospital care for people with dementia, their carers and families. Persons living with dementia, carers and family members were involved in the study through community dementia cafés and recruited to take part in focus groups to discuss hospital care for patients with dementia. The design of questions and materials for the discussions was developed through consultation with the university department's service user lead and dementia specialist and reviewed by a service user member living with dementia. A pilot focus group was conducted with a group of carers. We worked with the dementia café managers to coordinate recruitment and a suitable environment to run the focus groups. Trial Registration Not applicable.